Pentecostalism and Traditional Identity among the Urum of Southeastern Nigeria - Ugwu, Ugochukwu T; Nnatu, Stella Obioma; Chinweuba, Adaeze E. (Social Science Research, 2024)
There has been proliferation of Pentecostal churches and proselytizing in Nigeria. However, little is known empirically about how Pentecostalism affects the traditional religious identities of the rural dwellers in southeast Nigeria. In light of this, this study investigated how Pentecostalism affects traditional identity of the Urum of Southeastern Nigeria. The theoretical framework is structuralism. The study used mixed method research design. 203 is the sample size for the quantitative data while 4 participants were purposively selected as sample for the qualitative data. The study found that Pentecostalism has affected traditional identity through aggressive proselytizing thereby orchestrating unhealthy relationship among pentecostalists and non-pentecostalists. The study recommends governments interventions with intent to enforce relevant laws against noise pollution and should also arrest and prosecute religious and traditional leaders engaging in fake healing and fake miracles. Pentecostal and traditional believers should learn to cohabit peacefully, among others.